The compleat works of that eminent minister of Gods word Mr. Isaac Ambrose, consisting of these following treatises, viz. prima, media et ultima: or, the first, middle and last things. Wherein is set forth: I. The doctrine of regeneration, or the new birth. II. The practice of sanctification, in the means, duties, ordinances, both private and publick, for continuance and encrease of a godly life. III. Certain meditations of mans misery, in his life, death, judgement, and execution: as also of Gods mercy, in our redemption, and salvation. With a sermon added, concerning redeeming the time. Looking unto Jesus , as carrying on the great work of mans salvation. War with devils, ministration of, and communion with angels. [electronic resource] : (1674)
Summary goes here